Contemporary perspectives on research in educational assessment - Khine, Myint Swe (Emerald Publishing Limited : Information Age Publishing, Inc., 2020)
"Assessment and evaluation have always been an integral part of educational process. Quality and purposeful assessment can assist in students' learning and their achievement. While there has been a rapid growth in international, standardized student assessments in the past few decades, a large number of education systems participating in these assessments are now focusing their attention on developing new national, within-country assessments to evaluate educational standards and to modify the curriculum to better suit to the demands of the 21st century. Education systems that are successful in linking the national curriculum and assessments directly to international standards are performing better on international standardized assessments of reading, mathematics, and science. This book covers studies related to educational assessment in addressing quality of education and performance improvement. The book presents the distinguished and exemplary works by educators and researchers in the field highlighting the contemporary trends and issues, creative and unique approaches, innovative methods, frameworks, pedagogies and theoretical and practical aspects in assessment processes in various educational settings"-- Provided by publisher.
Includes index.
Keywords: Educational evaluation.; Academic achievement.; Curriculum planning.; Education -- Standards.; Education -- Aims & Objectives.; Education: examinations and assessment.; Educational strategies and policy.; elektronické knihy; electronic books